Employability skills performance score for fresh engineering graduates in Malaysian industry - Md Yusoff Y.; Omar M.Z.; Zaharim A.; Mohamed A.; Muhamad N. (2023)
This paper presents a method to evaluate the performance score based on employability skills for new engineers using NSW - Normalised Skill Weight. NSW is calculated from data collected from 337 employers of engineering industries in Kelang Valley, Malaysia. A questionnaire constructed to collect employers' perspectives regarding the level of requirement for each employability skills based on their needs. Twelve types of businesses related to engineering field engaged in the survey. In an earlier publication, in EDUCON2011, the authors have presented the employability skills for an entry-level engineer as seen by Malaysian employers. The finding shows the rank of skills according to the level of requirement and there are weight differences among the skills required by the industries. The result of analysis offers a suggestion for employers and undergraduates to calculate employability skills score based on the Normalised Skill Weight performed by engineering graduates. Furthermore, employers, who need to evaluate the quality of engineering graduates during interviews, might find this approach as key performance score for the assessment process to select new engineers.